Numerical algorithms of the radiative transport equation using rotated reference frames for optical tomography with structured illumination. (September 2019) - Machida, Manabu
Highlights: Optical tomography in spatial-frequency domain is considered. The radiative transport equation is used instead of the diffusion equation. Efficient numerical algorithms based on analytical solutions are presented. Abstract: We consider optical tomography with structured illumination in spatial-frequency domain using the three-dimensional radiative transport equation. Without the diffusion approximation, the radiative transport equation is solved by the technique of rotated reference frames. In addition to the method of rotated reference frames (spherical-harmonic expansion), the three dimensional FN method is applied to this optical tomography.